Regeneration of Vigna radiata (L.) Wilczek via callus and ability for water stress tolerance of callus lines - Thanh, Nguyen Vu Thanh; Mau, Chu Hoang (Academia Journal of Biology, 2012)
In this paper, we present results on plant regeneration in mungbean and drought tolerance at cullus level of eight mungbean cultivars (VN93-1; VN99-3; VC1973A; VC3902A; VC6148; VC6372; VC2768A, ĐX06). Vigna radiata (L.) Wilczek were regenerated via callus. The calli were formed from embryos on cullus induction medium (MS+10 mg/l 2,4D for VN93-1; VN99-3; VC1973A; VC3902A; VC6148; VC6372; VC2768A or MS+11 mg/l 2,4D for ĐX06). The formed calli were transfered onto shoots regeneration medium. MS medium added with 3 mg/l BAP was most suitable for shoot regeneration. Rate of shoot regeneration was from 77.3% to 98.6%. The MS medium added with 0.3 mg/l α-NAA gave the highest rate of  root and plant formation. 289 dehydration-tolerent callus lines and 715 plant lines have been generated.